Le paradigme du don face aux nouvelles réalités du monde du travail - Alain Caillé (La Nouvelle Revue du Travail)
Alain Caillé starts by resituating the gift paradigm that the “Anti-Utilitarian Social Sciences Movement” (Mouvement anti-utilitariste en sciences sociales, MAUSS) has tried to mobilise for nearly 30 years now. He then goes on to show how seeing things through the filter of gift-making makes it easier to see what lies in organisations’ black box, starting with the ravages of neo-management. Norbert Alter has written a response to this contribution under the aegis of his “Conceptualising work as a gift” (Peut-on penser le travail par le don?) Chorus file.